Investigation of the Optimum Machining Strategy for Steam and Gas Turbine Blades - Asariotakis Panagiotis-Andreas (2016)
Introduction, Thesis Overview, Aims and Objectives, Literature Review, Basic Theory, State of the Art, Experimental Methodology and Background, Turbine Blade Background, Milling Machining Background, CAD CAM Configuration, Experiment Implementation, Initial Actions, Roughing Operation, Foil Roughing Operation, Foil Finishing Operation, Root Operation, General Finishing Operation, Comparing and Ranking the Results, Roughing Process, Foil Roughing Process, Foil Finishing Process, Root Roughing Process, General Finishing Process, Final Ranking, Final Results and Proposals, References, Bibliography, Appendices, Meeting Log Form.